Age related, structured educational programmes for the management of atopic dermatitis in children and adolescents: multicentre, randomised controlled trial. Issue 7547 (20th April 2006) - Staab, Doris; Diepgen, Thomas L; Fartasch, Manigé; Kupfer, Jörg; Lob-Corzilius, Thomas; Ring, Johannes; Scheewe, Sibylle; Scheidt, Reginald; Schmid-Ott, Gerhard; Schnopp, Christina; Szczepanski, Rüdiger; Werfel, Thomas; et al.
Abstract: Objective To determine the effects of age related, structured educational programmes on the management of moderate to severe atopic dermatitis in childhood and adolescence. Design Multicentre, randomised controlled trial. Setting Seven hospitals in Germany. Participants Parents of children with atopic dermatitis aged 3 months to 7 years (n = 274) and 8-12 years (n = 102), adolescents with atopic dermatitis aged 13-18 years (n = 70), and controls (n = 244, n = 83, and n = 50, respectively). Interventions Group sessions of standardised intervention programmes for atopic dermatitis once weekly for six weeks or no education (control group). Main outcome measures Severity of eczema (scoring of atopic dermatitis scale), subjective severity (standardised questionnaires), and quality of life for parents of affected children aged less than 13 years, over 12 months. Results Significant improvements in severity of eczema and subjective severity were seen in all intervention groups compared with control groups (total score for severity: age 3 months to 7 years - 17.5, 95% confidence intervals - 19.6 to - 15.3 v - 12.2, - 14.3 to - 10.1; age 8-12 years - 16.0, - 20.0 to - 12.0 v - 7.8, - 11.4; - 4.3; and age 13-18 years - 19.7, - 23.7 to - 15.7 v - 5.2, - 10.5 to 0.1). Parents of affected children aged less than 7 years experienced significantly better improvement in all five quality of life subscales, whereas parents of affected children aged 8-12 years experienced significantly better improvement in three of five quality of life subscales. Conclusion Age related educational programmes for the control of atopic dermatitis in children and adolescents are effective in the long term management of the disease.